2016
DOI: 10.1098/rsob.160091
|View full text |Cite
|
Sign up to set email alerts
|

Atf3 mutant mice show reduced axon regeneration and impaired regeneration-associated gene induction after peripheral nerve injury

Abstract: Axon injury in the peripheral nervous system (PNS) induces a regeneration-associated gene (RAG) response. Atf3 (activating transcription factor 3) is such a RAG and ATF3's transcriptional activity might induce ‘effector’ RAGs (e.g. small proline rich protein 1a (Sprr1a), Galanin (Gal), growth-associated protein 43 (Gap43)) facilitating peripheral axon regeneration. We provide a first analysis of Atf3 mouse mutants in peripheral nerve regeneration. In Atf3 mutant mice, facial nerve regeneration and neurite outg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
83
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 85 publications
8
83
1
Order By: Relevance
“…436 20 To determine if Atf3 in sensory neurons is necessary for injury-induced 437 transcriptional reprogramming and sensory neuronal regeneration after injury, we 438 generated a floxed Atf3 mouse and crossed it with Vglut2-Cre mice (Figures 7A), resulting 439 in a conditional knockout (cKO) of Atf3 from >95% of sensory neurons (Atf3 WT: 89 ± 1% 440 of DRG neurons 1 week after SpNT are ATF3+ Nissl+; Atf3 cKO: 4 ± 2% of DRG neurons 441 1 week after SpNT are ATF3+ Nissl+; n=4 DRG sections, p<0.001, two-tailed Student's 442t-test) (Figure 7B). Consistent with a role for Atf3 in axonal regeneration(Gey et al, 2016; 443 Jing et al, 2012;Seijffers et al, 2006), the deletion of Atf3 in sensory neurons resulted in 444 a significant delay in functional sensory recovery after sciatic crush injury (Figure 7C), an 445 effect that we also observed using a tamoxifen-inducible cKO approach in the adult 446 mouse (Figures S7B-C). 447…”
supporting
confidence: 73%
“…436 20 To determine if Atf3 in sensory neurons is necessary for injury-induced 437 transcriptional reprogramming and sensory neuronal regeneration after injury, we 438 generated a floxed Atf3 mouse and crossed it with Vglut2-Cre mice (Figures 7A), resulting 439 in a conditional knockout (cKO) of Atf3 from >95% of sensory neurons (Atf3 WT: 89 ± 1% 440 of DRG neurons 1 week after SpNT are ATF3+ Nissl+; Atf3 cKO: 4 ± 2% of DRG neurons 441 1 week after SpNT are ATF3+ Nissl+; n=4 DRG sections, p<0.001, two-tailed Student's 442t-test) (Figure 7B). Consistent with a role for Atf3 in axonal regeneration(Gey et al, 2016; 443 Jing et al, 2012;Seijffers et al, 2006), the deletion of Atf3 in sensory neurons resulted in 444 a significant delay in functional sensory recovery after sciatic crush injury (Figure 7C), an 445 effect that we also observed using a tamoxifen-inducible cKO approach in the adult 446 mouse (Figures S7B-C). 447…”
supporting
confidence: 73%
“…35 This RAG response, via the activation of transcription factors such as STAT3, ATF3, and C-jun, promotes the synthesis of regeneration-associated molecules, including neuropeptides such as VIP. 36 This finding is also in agreement with previous observations of a superficialization of cholinergic fibers during regeneration in murine models of regeneration after a nerve injury. 14,37 The VIP-positive fibers observed in the upper dermis were unmyelinated and thin (1μm or less).…”
Section: Discussionsupporting
confidence: 93%
“…Recently, it has been demonstrated that the regeneration of peripheral injured axons is associated with the activation of a regeneration‐associated gene (RAG) response . This RAG response, via the activation of transcription factors such as STAT3, ATF3, and C‐jun, promotes the synthesis of regeneration‐associated molecules, including neuropeptides such as VIP . This finding is also in agreement with previous observations of a superficialization of cholinergic fibers during regeneration in murine models of regeneration after a nerve injury .…”
Section: Discussionsupporting
confidence: 88%
“…For example, JNK signalling leads to the activation of JUN and increased expression of the cAMP-dependent transcription factor ATF3 (REFS 55,108,109 ). In DRG neurons, JUN activation occurs in response to peripheral, but not central, axon injury 51 .…”
Section: Transcriptional Changesmentioning
confidence: 99%